2021
DOI: 10.3390/radiation1030020
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Radiation Therapy for COVID-19: A Systematic Review

Abstract: The ongoing COVID-19 pandemic is of great concern for the whole world, and finding an effective treatment for the disease caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is, therefore, a global race. In particular, treatment options for elderly patients and patients with genetic risk factors with COVID-19-associated pneumonia are limited, and many patients die. Low-dose radiotherapy (LDRT) of lungs was used to treat pneumonia many decades ago. Since the first report on the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…These results agree with those published previously. Several groups, including our own, have shown that whole-lung radiation at doses of 0.5–1.5 Gy can accelerate the recovery in clinical and radiographic status without acute toxicity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The appearance of new variants and the high degree of vaccination in most high-income countries has changed the scenario since 2020, towards a less severe disease and therefore, the usefulness of LDRT may be lower in the future than in these recent years.…”
Section: Discussionmentioning
confidence: 99%
“…These results agree with those published previously. Several groups, including our own, have shown that whole-lung radiation at doses of 0.5–1.5 Gy can accelerate the recovery in clinical and radiographic status without acute toxicity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. The appearance of new variants and the high degree of vaccination in most high-income countries has changed the scenario since 2020, towards a less severe disease and therefore, the usefulness of LDRT may be lower in the future than in these recent years.…”
Section: Discussionmentioning
confidence: 99%
“… 39 - 41 Therefore, the anti-inflammatory effects of localized radiation via alpha particles as well as the effect of low doses of radiation on reducing the risk of thrombosis are possibly involved in the lower number of hospitalized smokers than expected. 23 , 42 , 43 …”
Section: Radiation Energy Depositionmentioning
confidence: 99%
“…The sudden outbreak of SARS-CoV-2 infections results in COVID-19 disease, which is associated with compromised immunological defense and lung damage[ 38 ]. Therefore, the COVID-19 patients were isolated/quarantined and provided with medication and supplements to boost their immune mechanism to overcome the disease[ 39 ]. In addition to the boosters to immune mechanisms, several therapy strategies were tested to prevent viral entry, inhibition of virus replication, immunomodulatory agents, immunoglobulin therapy, vaccines, and potential control measures[ 28 ].…”
Section: Low Dose X-radiation Therapy (Ldrt) For the Management Of Co...mentioning
confidence: 99%
“…One of those therapy strategies is the use of LDRT for COVID-19-infected patients because it has been proven to cure pneumonia in the early 20 th century[ 40 ]. The treatment with low-dose X-rays complements other treatment modalities and has a profound role in minimizing COVID-19 infection severity[ 39 ]. Low dose comprises doses below 100 mGy as defined by UNSCEAR and has the characteristics such as accelerated immune senescence, altered immune fitness, a shift in peripheral lymphocyte, balance in favor of B-cells, and pro-inflammatory responses[ 39 ].…”
Section: Low Dose X-radiation Therapy (Ldrt) For the Management Of Co...mentioning
confidence: 99%
See 1 more Smart Citation